Pseudorapidity and transverse-momentum distributions of charged particles in proton-proton collisions at √s=13 TeV - Adam, Jaroslav; Angelov, Venelin; Bock, Friederike; Busch, Oliver; Deisting, Alexander; Fleck, Martin; Glässel, Peter; Karayan, Lilit; Klewin, Sebastian; Knichel, Michael Linus; Leardini, Lucia; Mercado Pérez, Jorge; et al. (Physics letters, 2016)
The pseudorapidity (η) and transverse-momentum (pT) distributions of charged particles produced in proton-proton collisions are measured at the centre-of-mass energy s=13 TeV. The pseudorapidity distribution in |η|<1.8 is reported for inelastic events and for events with at least one charged particle in |η|<1. The pseudorapidity density of charged particles produced in the pseudorapidity region |η|<0.5 is 5.31±0.18 and 6.46±0.19 for the two event classes, respectively. The transverse-momentum distribution of charged particles is measured in the range 0.15<pT<20 GeV/c and |η|<0.8 for events with at least one charged particle in |η|<1. The evolution of the transverse momentum spectra of charged particles is also investigated as a function of event multiplicity. The results are compared with calculations from PYTHIA and EPOS Monte Carlo generators.
Im Titel steht der Ausdruck "s" unter dem Wurzelsymbol
ALICE collaboration: J. Adam, V. Anguelov, F. Bock, O. Busch, A. Deisting, M.G. Fleck, P. Glässel, L. Karayan, S. Klewin, M.L. Knichel, L. Leardini, J. Mercado Pérez, H. Oeschler, K. Oyama, Y. Pachmayer, F. Reidt, K. Reygers, R. Schicker, J. Stachel, J.H. Stiller, M.A. Völkl, D.F.Weiser, J. Wilkinson, B. Windelband, M. Winn, A. Zimmermann [und 961 weitere]
Available online 15 December 2015
Gesehen am 29.07.2020